Evaluation of interannual variability of Arctic and Antarctic ozone loss since 1989 - Goutail, Florence; Pazmino, Andrea; Pommereau, Jean-Pierre; Lefèvre, Franck; Godin-Beekmann, Sophie; Hauchecorne, Alain; Lecouffe, Audrey; Clerbaux, Cathy; Boynard, Anne; Hadji-Lazaro, Juliette; Chipperfield, Martyn; Feng, Wuhu; et al. (2021)
Ozone depletion over Polar Regions is monitored each year by satellite and ground-based instruments. The first signs of healing of the ozone layer linked to the decrease of ozone destructive substances (ODSs) were observed in Antarctica using different metrics (ozone mean values, ozone mass deficit, area of the ozone hole) and simple or sophisticated models. Chemistry climate models predict that climate change will not affect expected ozone recovery over Antarctica but will accelerate recovery in the Arctic due to the possible enhancement of the Brewer Dobson circulation. However, ozone loss observations by SAOZ UV-Vis spectrometers do not show a clear sign of recovery in the latter region. In addition, a record of 38% ozone loss in 2010/2011 and 2019/2020 was estimated. In this study, the vortex-averaged ozone loss in the last three decades will be evaluated for both Polar Regions using the passive ozone tracer of two chemical transport models (REPROBUS and SLIMCAT CTMs) and total ozone observations from SAOZ and satellite observations (IASI/METOP and Multi-Sensor Reanalysis (MSR-2)). The tracer method allows us to determine the evolution of the daily rate of ozone destruction, and the amplitude of the cumulative loss at the end of the winter. The cumulative ozone destruction in the Artic varies between 0-10% in relatively warm winters with short vortex duration to up to 25-38% in colder winters with longer vortex persistence, while in Antarctica it is mostly stable, around 50%. Interannual variability of 10-days average rate will be analyzed and compared between both hemispheres as well as the timing to reach different thresholds of absolute ozone loss values. Finally, linear trend of ozone loss and temperature since 2000 will be estimated in both Polar Regions in order to evaluate possible ozone recovery.
Keywords: Antarktis; klimaendringer; miljøovervåking; ozonlaget; polarområdene

Forskrift om etablering, drift og bruk av jordstasjon for satellitt i Antarktis - Kommunaldepartementet (Lovdata, 2017)
Keywords: Dronning Maud Land; jus; kommunikasjon; teknologi

Forskrift om miljøvern og sikkerhet i Antarktis - miljødepartementet, Klima- og (Lovdata, 2013)
Keywords: Antarktis; Dronning Maud Land; forurensning; forvaltning; jus; miljøvern; naturvern

Forskrift om miljøvern og sikkerhet i Antarktis - Miljøverndepartementet (Justisdep., 2013)
Keywords: Antarktis; jus; miljøvern

Geological map of Heimefrontfjella, Dronning Maud Land, Antarctica (Scale 1:250,000) - Jacobs, Joachim; Bauer, Wilfried; Kreutzer, Stefan; Patzelt, Gernot; Schmidt, Rainer; Schulze, Peter; Siegesmund, Siegfried; Spaeth, Gerhard; Thomas, Robert J; Weber, Klaus; Zarske, Gerd (PANGAEA, 2009)
The geological overview map was compiled from 15 geological maps (1 : 25,000) and is based on Jacobs et al. 1996. The topographic basemaps were adapted from unpublished 1:250,000 provisional topographic maps, Institut f. Angewandte Geodäsie, Frankfurt, 1983. Part of the contour lines are from Radarsat (Liu et al. 2001).
Keywords: Dronning Maud Land; geologi; kart; topografi

Forskrift om ferdselsbegrensning i Nyrøysaområdet på Bouvetøya - miljødepartementet, Klima- og (Lovdata, 2005)
Keywords: Bouvetøya; naturvern

Forskrift om grunnlinjen for sjøterritoriet ved Bouvetøya - Utenriksdepartementet (Lovdata, 2005)
Keywords: Bouvetøya; forvaltning; jus

Forskrift om regulering av fiske med norske fartøyer i Antarktis (CCAMLR-området) - fiskeridepartementet, Nærings- og (Lovdata, 1998)
Keywords: Sørishavet; fiskeri; jus

Kvitkuven: Kronprinsesse Märtha Kyst (Norsk Polarinstitutt, 1997)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1997)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1997)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Breeding biology and diet of pintado petrels Daption capense at Bouvetøya during the summer of 1996/97 - Huyser, Onno; Dyer, Bruce M; Isaksen, Kjell; Ryan, P; Cooper, J (Commission for the Conservation of Antarctic Marine Living Resources, 1997)
Keywords: Bouvetøya; ornitologi; petreller; reproduksjon; zoologi

Establishment of a CEMP-monitoring program at Bouvetøya - Isaksen, Kjell; Bakken, Vidar; Gjertz, Ian; Mehlum, Fridtjof (Commission for the Conservation of Antarctic Marine Living Resources, 1997)
Keywords: Bouvetøya; forskningsstasjoner; overvåking; pingviner; seler; zoologi

Preliminary results from CEMP monitoring of Antarctic fur seals, chinstrap penguins and macaroni penguins at Bouvetøya 1996/97 - Isaksen, Kjell; Hofmeyr, Greg J G; Dyer, Bruce M; Næstvold, Alf; Mehlum, Fridtjof; Gjertz, Ian; Bakken, Vidar; Huyser, Onno (Commission for the Conservation of Antarctic Marine Living Resources, 1997)
Keywords: Bouvetøya; forskningsstasjoner; overvåking; pingviner; seler; zoologi

Ahlmannryggen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulstraumen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Nature environment map: Gjelsvikfjella and Western Mühlig-Hofmannfjella, Dronning Maud Land, Antarctica - Høgvard, K (Norsk Polarinstitutt, 1993)
Keywords: Dronning Maud Land; NARE 1984/85; NARE 1989/90; geografi; kartlegging

Jutulsessen: Fimbulheimen (Norsk Polarinstitutt, 1992)
Keywords: Dronning Maud Land; Troll forskningsstasjon; geografi; kartlegging; satellite bilder

Samtykke til ratifikasjon av Protokoll om miljøvern til Antarktistraktaten, undertegnet i Madrid 4. oktober 1991 - Utenriksdepartementet (1992)
Keywords: Antarktis; forvaltning; miljøvern; politikk

H.U. Sverdrupfjella: Fimbulheimen (Norsk Polarinstitutt, 1991)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1991)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Mühlig-Hofmannfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1991)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Mühlig-Hofmannfjella Sør: Fimbulheimen (Norsk Polarinstitutt, 1991)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Heimfrontfjella Nord: Maudheimvidda (Norsk Polarinstitutt, 1988)
Keywords: Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Heimfrontfjella Sør: Maudheimvidda (Norsk Polarinstitutt, 1988)
Keywords: Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Namnemanus Peter I Øy (Norsk Polarinstitutt, 1988)
Keywords: Peter I. Øy; geografi; kartlegging

Journal over den Belgiske Sydhavs-Expedition 97-99 - Koren, Johan (1988)
Keywords: Antarktis; Belgica (skip); dagbok; oppdagelsesreiser; overvintring; polarekspedisjoner

Flichnerfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1984)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Konvensjon om bevaring av marine levende ressurser i Antarktis = Convention on the Conservation of Antarctic Marine Living Resources (Lovdata, 1980)
Keywords: Sørishavet; forvaltning; jus; marinbiologi; miljøvern; naturvern

The work of SCAR for the conservation of nature in the Antarctic - Gjelsvik, Tore (University of Chile, 1977)
Keywords: Antarktis; fauna; flora; forurensning; kongress; miljø; politikk; symposium; økologi

Norwegian Antarctic Research. Past and Present. - Orheim, Olav (University of Chile, 1977)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; NARE ekspedisjoner; Weddellhavet; geologi; glasiologi; havis; hvalfangst; kongress; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; symposium

Forposten: Fimbulheimen (Norsk Polarinstitutt, 1975)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Annandagstoppane. Maudheimvidda (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; geografi; kartlegging

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Forskrift om fredning av Bouvetøya med tilliggende territorialfarvann som naturreservat - miljødepartementet, Klima- og (Lovdata, 1971)
Keywords: Bouvetøya; jus; miljøvern; naturvern

Sydishavet og tilgrensende områder: Blad 11 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1964)
Keywords: Norsel (skip); Sørishavet; geografi; kartlegging

Kronprinsesse Märtha Kyst - Maudheimvidda: Dronning Maud Land (Norsk Polarinstitutt, 1963)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Maudheimvidda Aust: Dronning Maud Land (Norsk Polarinstitutt, 1963)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Borgmassivet: Maudheimvidda (Norsk Polarinstitutt, 1962)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Giæverryggen: Maudheimvidda (Norsk Polarinstitutt, 1962)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Noteveksling mellom Norges regjering og Sør-Afrika-Sambandets regjering angående lån til Sør-Afrika-Sambandet av Norway Station beliggende i det norske biland Dronning Maud Land - Utenriksdepartementet (Statsrådsekretariatet, 1960)
Keywords: Dronning Maud Land; jus; politikk; stasjoner

Dronning Maud Land: Sør-Rondane - Luncke, Bernhard (Norsk Polarinstitutt, 1957)
Keywords: Antarktiske ekspedisjon 1946-47; Dronning Maud Land; Richard Evelyn Byrd; flyfoto; geografi; kartlegging; luftfoto

Sydishavet: Blad 2 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1950)
Keywords: Bouvetøya; Dronning Maud Land; Sørishavet; geografi; kartlegging

Sydishavet og tilgrensende farvann: Blad 12 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1949)
Keywords: Sørishavet; geografi; hvalfangst; kartlegging

Antarktis/Antarctica: Kart nummer 7 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Keywords: Antarktis; Lars Christensen; ekspedisjoner; flyfoto; geografi; kartlegging; luftfoto

Sydishavet (Blad 5) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 7) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 8) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Keywords: Sørishavet; geografi; kartlegging

Atlas over dele av det antarktiske kystland = Atlas of parts of the Antarctic coastal lands - Hansen, Hans Edvard; Luncke, Bernhard (Grøndahl, 1946)
Keywords: Antarktis; Lars Christensen; Sørishavet; Thorshavn ekspedisjon; flyfoto; kartlegging; luftfoto

Sydishavet - Balleny öyene (Blad 3) (Hvalfangernes Assuranceforening, 1937)
Keywords: Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet - Hearst Land, Charcot ö (Blad 4) (Hvalfangernes Assuranceforening, 1937)
Keywords: Norvegia ekspedisjoner; Peter I. Øy; Sørishavet; geografi; kartlegging

Sydishavet - Kong Haakon VII Hav (Blad 1) (Hvalfangernes Assuranceforening, 1937)
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; Thorshammer ekspedisjon; geografi; kartlegging

Sydishavet - Kronprins Olav Land (Blad 2) (Hvalfangernes Assuranceforening, 1937)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; Thorshavn ekspedisjon; geografi; kartlegging

Sydishavet (Blad 6) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1937)
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 7) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1937)
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 8) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1937)
Keywords: Sørishavet; geografi; kartlegging

Antarktis og Sydishavet (Norwegian Mapping Authority / Kartverket, 1936)
Keywords: Antarktis; Jason ekspedisjonene; Norvegia ekspedisjoner; Odd I; Sørishavet; Thorshavn ekspedisjon; ekspedisjonen; geografi; kartlegging

Sydishavet (Blad 1) (Hvalfangernes Assuranceforening, 1936)
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; geografi; kartlegging

Bunnen av Weddellhavet (Hvalfangernes Assuranceforening, 1935)
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet (Blad 2) (Hvalfangernes Assuranceforening, 1935)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Sørishavet; Thorshavn ekspedisjon; geografi; kartlegging

Sydishavet - Weddel Havet - Kong Haakon VII hav (Blad 1) (Hvalfangernes Assuranceforening, 1935)
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet (Blad 2) (Hvalfangernes Assuranceforening, 1933)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet (Blad 3) (Hvalfangernes Assuranceforening, 1933)
Keywords: Antarktis; Sørishavet; ekspedisjoner; geografi; kartlegging

Sydishavet - Weddel Havet - Kong Haakon VII hav (Blad 1) (Hvalfangernes Assuranceforening, 1933)
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Norvegia-ekspedisjonen 1930-1931 (Norges geografi oppmåling, 1931)
Keywords: Antarktis; Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet - Kong Haakon VII hav (Norges geografi oppmåling, 1931)
Keywords: Antarktis; Sørishavet; ekspedisjoner; geografi; kartlegging

Lov om Bouvet-øya, Peter I's øy og Dronning Maud Land m.m. (bilandsloven) (Lovdata, 1930)
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; jus; lovgivning

Forskrift om Bouvet-øya - Justisdepartementet (Lovdata, 1930)
Keywords: Bouvetøya; jus

[Kart over Antarktika og Sydishavet]. Skisser med "Odd" og "Norvegia" sine ruter i Antarktis 1927-1929 - [Aagaard, Bjarne] (1929)
Keywords: Antarktis; Norvegia ekspedisjoner; Odd I; Sørishavet; ekspedisjonen; geografi; kartlegging

Peter I Øy - Larsen, Nils (1929)
Keywords: Lars Christensen; Norvegia ekspedisjonen; Peter I. Øy; geografi; kartlegging

Dagbok: "Den tredje Framfærd. 7de juni 1910 - 6de mars 1912" - Amundsen, Roald (Nasjonalbiblioteket, 1912)
Keywords: Antarktis; Roald Amundsen; Sydpolen; dagbøker; ekspedisjoner; oppdagelsesreiser

"Dagbog tilhørende Fredrik Hjalmar Johansen, ført på 3die Framexpedition, påbegyndt efter afgangen fra Norge, 15de august 1910 til 14de januar 1912" - Johansen, Hjalmar (Nasjonalbiblioteket, 1912)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; oppdagelsesreiser

Parry Mountains - Collier, William; Borchgrevink, Carsten Egeberg
Keywords: Antarktis; Southern Cross; ekspedisjonen; geografi; kartlegging

Robertson Bay, South Victoria Land - Collier, William; Borchgrevink, Carsten Egeberg
Keywords: Antarktis; Southern Cross; ekspedisjonen; geografi; kartlegging

Southern Cross from Hobart to Cape Adare - Collier, William; Borchgrevink, Carsten Egeberg
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Kapp Adare; Southern Cross; ekspedisjonen; geografi; kartlegging

Polar Ponies: The Forgotten Story of Antarctica’s Meat-Eating Horses - O’Reilly, CuChullaine (The Long Riders Guild Academic Foundation)
While it is now commonly agreed that dog travel in winter conditions is an excellent methodology, abundant evidence demonstrates that this view was not shared by all polar explorers at the beginning of the last century. What has also been overlooked is the simultaneous use of meat-eating horses in trying to reach both the North and South Poles.
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie